Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi dan Penggunaan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pada BUMDES Se-Kabupaten Klungkung - Pradnya Putri, I Gusti Ayu Eka; Sumadi, Ni Komang; Pratiwi, Ni Putu Trisna Windika (UNHI Press, 2025)
An entity's management of financial resources is accounted for through the quality of its financial statements. Structured reports on the financial position and transactions completed and reported by a reporting entity characterise the quality of financial statements. Financial statements are considered high quality and valuable to various users if the data presented are understandable, relevant, reliable and comparable. The level of education, accounting knowledge, and the use of information technology are some of the variables that affect the quality of financial statements. The purpose of this study was to examine the effect of education level, accounting knowledge, and use of technology on the quality of financial reports produced by BUMDes throughout Klungkung Regency. Using primary data, this study employed quantitative research methodology. A total of 238 BUMDes employees in Klungkung Regency became the population of this study. Purposive sampling was used in this study to determine the sample size, which resulted in 54 respondents. The research findings show that the level of education significantly and positively affects the quality of financial statements. The quality of financial statements is positively and significantly influenced by accounting knowledge. The quality of financial statements is not affected by the use of information technology. Based on the findings of the current study, it is anticipated that by determining technology needs, improving infrastructure, educating system users, and conducting frequent assessments, the use of technology will increase.